Pre-Surgical Planning Using Virtual And 3D Printing Model as Guidance for SECONDARY Mandible Reconstruction with Bone Graft: A Case Report - Christabela Dwiutami Tanto; Timotius Hansen Arista; Rionaldo Dhiparedja; Bambang Wicaksono (International Journal Labs, 2024)
Reconstruction of mandibular defects due to trauma or tumor resection is a significant challenge for surgeons, given the unique and variable shape of the mandible in terms of curvature, length, and height. Numerous techniques have been developed to achieve both aesthetic and functional outcomes. This case report presents a 28-year-old patient with mandibular irregularity following ameloblastoma dissection, which was reconstructed with non-vascularized bone grafts (NBGs) from the left iliac crest approximately 10 years ago. Prior to our procedure, virtual planning and 3D modeling were employed to accurately assess the bone defect. After debridement, a 5 cm defect was identified, and NBGs were harvested from the right iliac crest for reconstruction. NBGs are commonly used for small mandibular defects (<6 cm), non-continuity defects, and benign pathologies, and they can be performed in centers without microsurgical expertise. The use of virtual planning and 3D printing enables the surgical team to thoroughly study the case, anticipate potential issues, and improve precision, resulting in better outcomes and reduced operative time. NBGs, guided by virtual planning and 3D modeling, prove to be an effective technique in reducing surgical time and minimizing the risk of failure during the postoperative recovery period.